Biokinetics of arsenate accumulation and release in Microcystis aeruginosa regulated by common environmental factors: Practical implications for enhanced bioremediation. (20th October 2018) - Wang, Zhenhong; Luo, Zhuanxi; Yan, Changzhou; Rosenfeldt, Ricki R.; Seitz, Frank; Gui, Herong
Abstract: Only little information is available on combined effects of abiotic environmental factors on algal arsenate ( As V ) metabolic biokinetics. Using the Taguchi statistical method, we investigated four environmental factors including As V, nitrate (N), orthophosphate (P) and pH for their combined effects on algal growth and arsenic ( As ) uptake but also extracellular adsorption of Microcystis aeruginosa, as well as As release from dead algal cells. Results showed that an increase of N facilitated M. aeruginosa growth and thus was the principal factor for the algal maximum specific growth rate ( μ m a x ). P was vital to As V bioconcentration factor (BCF) and As partition coefficients (Log K d ) released from deal algal cells. As V impacted the extracellular As adsorption onto the algal cells, which thereby increased with increasing initial As V level. The initial pH had an imperative effect on the As V uptake ( k u ) and release rate ( K e ) from the dead cells. The optimum conditions on As V metabolic biokinetics were N at 10.0 mg L −1 for μ m a x, P at 0.02 mg L −1 for Log K d and BCF, As V at 10.0 μM for extracellular As adsorption, and pH at 10 for k u, BCF and extracellular As adsorption, but pH at 6 for K e . Collectively, the condition of low P, high N and alkaline pH level was favorable to As accumulation rate of living cells and restrictive to As release rate from dead cells of M. aeruginosa . The obtained information can pave a road for extensive understanding on efficient utilization of As bioremediation of algae in practical environment. Graphical abstract: Image 1 Highlights: Principal factors were identified on As V metabolic biokinetics by Taguchi method. P was critical to control As uptake in living cells and efflux levels in dead cells. N meaningfully impacted the As release rate in living and deal cells. As V only as the main factor impacted As extracellular adsorption on algal cells. High N and pH but low P fasten As V uptake and reduce As efflux from dead cells.